Pengaruh ROA, DER, dan Opini Audit terhadap Audit Delay Dimoderasi Reputasi KAP - Ariya Maulana Bakri; Liza Novietta (Forum Kerjasama Pendidikan Tinggi, 2026)
The research aims to determine the return on assets (ROA), debt to equity ratio (DER), and audit opinion on audit delay with the reputation of the Public Accounting Firm as a moderating variable in the study of consumer goods industry companies with the food and beverage sub-sector listed on the Indonesian Stock Exchange for the period 2019-2023. The sample selection method used is purposive sampling. The total observations in this study were 255 samples with 5 years of observation consisting of 51 companies. The data analysis technique used in this study is moderation analysis using moderated regression analysis. The research results found that return on assets, debt-to-equity ratio, and audit opinion influenced audit delay. Furthermore, the reputation of the public accounting firm did not moderate the influence of ROA, DER, and audit opinion on audit delay.